Acondicionamento de hidroxiapatita nanoparticulada em sachês biodegradáveis para aplicação como fertilizante mineral - Sciena, Camila Rodrigues (Universidade Federal de São Carlos, 2015)
In 2013, the portion of the Brazilian agrarian system in the gross domestic product reached 22.54% according to CEPEA. The production of agricultural commodities is extremely dependent on imported fertilizer, as 74.6% of the material used on national soil has foreign origin. In the case of phosphate fertilizers, the main route for production is by adding sulfuric acid to the phosphate rock, producing phosphoric acid and calcium sulfate, also known as phosphogypsum. This is a major environmental problem generator, since large quantities of by-product are stored without an end use. In order to minimize this issue, this work aims to examine the release of phosphate by hydroxyapatite (HAP) solubilization synthesized in the laboratory in order to assess your application as mineral fertilizer. Since the HAP have low solubility, it was aim at synthesizing a nanostructured material to aid its dissolution, since this property is, normally, dependent on the particle size. In order to minimize the effects of leaching of the soil material were processed blends of biodegradable starch and pectin for the production of sachets for packaging of HAP particulate as well as the slow release thereof. The hydroxyapatite used in this study was obtain by wet coprecipitation method followed by hydrothermal treatment or not. With the use of surfactants and variation in the hydrothermal treatment time, rod and whiskers morphology materials were obtain. For characterization of the synthesized samples was using an x-ray diffractometer. The results from this showed that the particles produced in this study are present in a single step without the occurrence of undesirable secondary phases. The FTIR and FTRaman confirmed the result obtained by XRD. From the Zeta potential was observed that the sample of smaller surface area is made more stable in solution than the rest of the analyzed compounds. It was also observe that increasing the crystallinity of the material resulted in a lower solubility at neutral pH thereof. The release assay was repeated at acidic pH, indicating that more acidic conditions lead to higher dissolutions of samples. From the release tests it was found that the samples had higher solubility at neutral pH, approximately 4.5 mg L-1 of phosphorus released, were smaller and less degree of crystallinity. For the larger and more crystalline sample solutions formed concentrations of at most 1.5 mg L-1. Since the tests made at acidic pH showed that the samples, regardless of the size and crystallinity presented are easily solubilized. All solutions obtained showed the phosphorus concentration around 15 mg L-1. Blends were used to condition the HAP, and chosen to be used in the present work was to TPS 75: 25 PEC, due to its greater flexibility and greater resistance in solution. The solubility obtained for the samples contained in the sachet showed high values, even at pH close to neutral, indicating its potential use.
Packaging hydroxyapatite nanoparticles in biodegradable sachets for use as mineral fertilizer
Keywords: Hidroxiapatita; Nanopartículas; Fósforo; CIENCIAS EXATAS E DA TERRA::QUIMICA::FISICO-QUIMICA